INVESTIGATING THE THEMES OF BODY CULTURE IN PHYSICAL EDUCATION CLASSES IN BARRA DO GARÇAS (Fiep Bulletin - online, 2012)
The Physical Education is a discipline that treats pedagogically in the school of knowledge of body culture that set inform of themes as games, sports, gymnastic, dance, fights, and others. Still what we can verify is that on Physical Educationclasses there is the prevalence of only some themes of body culture as the sports (volleyball, basketball, soccer and others). Withit the central objective of this study if identify the contents that are experienced by the students in Physical Education classes in5th to 8th grade in state schools of Barra do Garças – MT, with analysis of annual plans of the teachers and the politicalpedagogical project and by questionnaire to the students of all the public schools . In the area of investigation was consisted of 14schools. The subject of our search was 310 students in Physical Education teachers. We used questionnaires to investigate whatcontent experienced in class we analyze the PPP and the annual plans of the teacher and finally crossed this data with theComprehensive Curriculum of the State and the PCN. In the questionnaire with the students we had as result the dominant sportssuch as content more practiced in Physical Education classes. The annual planning with their contents was also restricted tosports, coinciding with the students answered the questionnaires. While PPPS ARE GOING AGAINST THE ProposedCurriculum and PCN. It is important to provide students with the knowledge of various issues of Physical Culture, so it hasconsciousness in Physical Education classes can develop all through your body.
Keywords: School; Body Culture; Physical Education